The effect of media exposure on contraceptive adoption across "poverty line". Issue 3 (7th September 2015) - Ramendra Singh, Dr; Khandeparkar, Kapil; Roy, Pinaki; Motiani, Manoj
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to explore the effect of mass media exposure on women contraceptive adoption. The intent was to show how factors affected contraceptive use, such as education, standards of living, etc., behave differently across the poverty line. Design/methodology/approach – Logistic regression was used to test the effect of exposure of various mass media on contraceptive adoption. Indian Human Development Survey (2005) was used for the analysis. Analysis was performed to compare results across the poverty line. Findings – Television exposure was found to be significant, and it had a strong effect on the likelihood that the family uses contraceptives. Newspaper readership was found significant above the poverty line and insignificant below. Research limitations/implications – The present study only analyzes cross-sectional data. A longitudinal study would be better suited to determine how these factors affect contraceptive use over time. Practical implications – The findings of this study can be useful in designing more effective media mix for the communications aimed at increasing contraceptive use in India. Social implications – The findings show the divide between the population segments above and below the poverty line. Low education levels, affordability issues and son preferences are the major factors deterring contraceptive use at this level. Originality/value – This is the first study to separately study the population samples across the poverty line. Compared to previous studies which focuses heavily on one media, this analysis includes other media variables and focuses on a variation of these factors across the poverty line.